THE RELATIONSHIP BETWEEN FINANCIAL REPORTING AGGRESSIVENESS AND TAX AUDIT RISK IN PUBLIC COMPANIES - Windy Permata Suyono; Eka Septariana Puspa; Surya Anugrah (INTERNATIONAL JOURNAL OF ECONOMIC LITERATURE, 2025)
This research aims to examine the relationship between financial reporting aggressiveness and tax audit risk in listed companies through a literature review approach. Aggressive financial reporting is a strategy used by companies to manipulate accounting numbers in order to achieve certain goals, including tax avoidance. This strategy has the potential to increase the risk of a tax audit because striking differences between commercial and fiscal financial statements may trigger the attention of tax authorities. Through a systematic review of various previous studies, it was found that the majority of research shows a positive relationship between these two variables, although the results vary depending on the institutional context, quality of governance, and company characteristics. This research also identified gaps in the literature, especially regarding the lack of studies in developing countries such as Indonesia and the lack of integration between accounting and tax perspectives.